The Queen's window by David Hockney, Westminster Abbey - Jenkins, Susan; Hockney, David; Hockney, David (Scala Arts & Heritage Publishers Ltd, 2020)
A fascinating exploration of the process of designing and making David Hockney?s Queen?s Window at Westminster Abbey, unveiled in October 2018. This is the first time Hockney has designed a work in stained glass, which he drew up on his trademark iPad. The artist chose to celebrate the reign of Her Majesty Queen Elizabeth II with his favourite emblem of Englishness, the hawthorn blossom of his native Yorkshire landscape. The commission was a collaboration between Westminster Abbey, the artist and Barley Studios in York, who made the stained glass